Inhibition of IP3R/Ca2+ Dysregulation Protects Mice From Ventilator-Induced Lung Injury via Endoplasmic Reticulum and Mitochondrial Pathways - Ye, Liu; Zeng, Qi; Ling, Maoyao; Ma, Riliang; Chen, Haishao; Lin, Fei; Li, Zhao; Pan, Linghui (Frontiers in Immunology, 2021)
Rationale Disruption of intracellular calcium (Ca2+) homeostasis is implicated in inflammatory responses. Here we investigated endoplasmic reticulum (ER) Ca2+ efflux through the Inositol 1,4,5-trisphosphate receptor (IP3R) as a potential mechanism of inflammatory pathophysiology in a ventilator-induced lung injury (VILI) mouse model. Methods C57BL/6 mice were exposed to mechanical ventilation using high tidal volume (HTV). Mice were pretreated with the IP3R agonist carbachol, IP3R inhibitor 2-aminoethoxydiphenyl borate (2-APB) or the Ca2+ chelator BAPTA-AM. Lung tissues and bronchoalveolar lavage fluid (BALF) were collected to measure Ca2+ concentrations, inflammatory responses and mRNA/protein expression associated with ER stress, NLRP3 inflammasome activation and inflammation. Analyses were conducted in concert with cultured murine lung cell lines. Results Lungs from mice subjected to HTV displayed upregulated IP3R expression in ER and mitochondrial-associated-membranes (MAMs), with enhanced formation of MAMs. Moreover, HTV disrupted Ca2+ homeostasis, with increased flux from the ER to the cytoplasm and mitochondria. Administration of carbachol aggravated HTV-induced lung injury and inflammation while pretreatment with 2-APB or BAPTA-AM largely prevented these effects. HTV activated the IRE1α and PERK arms of the ER stress signaling response and induced mitochondrial dysfunction-NLRP3 inflammasome activation in an IP3R-dependent manner. Similarly, disruption of IP3R/Ca2+ in MLE12 and RAW264.7 cells using carbachol lead to inflammatory responses, and stimulated ER stress and mitochondrial dysfunction. Conclusion Increase in IP3R-mediated Ca2+ release is involved in the inflammatory pathophysiology of VILI via ER stress and mitochondrial dysfunction. Antagonizing IP3R/Ca2+ and/or maintaining Ca2+ homeostasis in lung tissue represents a prospective treatment approach for VILI.